COVID-19: An Emerging Culprit of Inflammatory Arthritis. (26th April 2021) - Mukarram, Muhammad Shariq; Ishaq Ghauri, Muhammad; Sethar, Sehrish; Afsar, Nasir; Riaz, Amir; Ishaq, Khizra
Abstract : Arthralgia is one of the most common symptoms that occur in patients with COVID-19. About 15% of patients present with arthralgia at some point. Although COVID-19 seems to attack the musculoskeletal system (muscles and joints) in its infective and postinfective stage causing inflammatory arthritis, not much is known about the rheumatic manifestations of this infection. In this case series of 5 patients, we discuss the occurrence of bilaterally symmetrical polyarthritis in patients, previously free from any rheumatic disease, after encountering COVID-19 infection. The musculoskeletal manifestations in these patients phenotypically resembled rheumatoid arthritis. These patients were treated successfully with low-dose glucocorticoids and disease-modifying antirheumatic drugs (DMARDs).